The choice of the content of training process for mass-category athletes in view of the subjectivity of competitive activity - Orlov, Andrey I.; Talantseva, Valentina K.; Shilenko, Olga V.; Petrova, Tatyana N.; Kudratova, Lola A. (Физическое воспитание и студенческий спорт)
Currently, in the practice of mass sports, despite modern trends in its development, a conservative approach prevails when choosing means and methods of the training process for mass-category athletes. Based on the results of the research, it is stated that this approach has practically exhausted its development potential, which, in turn, brings to the surface the problem of searching the content of young athletes’ training process, potentially allowing to increase its effectiveness. It should be noted that this problem is most acute when choosing the content of the mass-category athletes’ training process at the stages of initial training and sports specialization. Whereas at the stages of sports mastery improvement and perfection, for a number of reasons, it is not so clearly defined. This can be confirmed by the success of Russian athletes in the international sports arena. The solution to the identified problem is proposed to be carried out in accordance with the principle of primacy of competitive activity in relation to training, which will allow us to identify specific features of the implementation of a concrete competitive exercise. Taking into account this requirement, the most common classifications of sports are analyzed, which, according to the authors, will allow not only to determine the place of each of them in their systemic diversity, but also to select more relevant means of sports training. In this context, it is noted that the most common classifications of sports, reflecting mainly the biomechanical and physiological characteristics of competitive activity, do not allow the phenomenology of a particular sport to be fully realized. Based on this, it would be possible to expand understanding of the nature of competitive activity and thereby the arsenal of training tools and methods. In addition to the already existing classifications of sports, an original approach is proposed, in which the nature of the main interaction when performing a competitive exercise is considered as a classification feature. Within its framework, a matrix has been developed that reflects subject-subject and subject-object sports, which are also divided into team and individual. Within the developed matrix, a brief psychological characteristic of sports and competitive exercises is given. Taking into account the systematic approach, coupled with the highlighted subjectivity of competitive activity, it seems possible to theoretically substantiate the need to implement in the training process of mass-category athletes the means of targeted development of attention properties that predetermine the effectiveness of competitive actions, and problembased teaching methods in the formation of the ability to plan competitive activity.